Diversitas dan Kelimpahan Lalat Buah (Bactrocera sp) terhadap Kerusakan Tanaman Tomat (Solanum lycopersicum L.) - Hasinu, Jeffij V.; Tuhumury, Gratiana N.C. (JURNAL PERTANIAN KEPULAUAN, 2025)
AbstractThis research aims to analyze the diversity of fruit flies (Bactrocera sp.) and their damage to tomato plantings. The research was carried out in Ouw village, East Saparua District, Central Maluku Regency. This research was a quantitative descriptive study carried out using a survey method with ME traps, which were applied directly in the field using Steiner Trap Type II traps. Data analysis includes the Diversity Index, Relative Density, Evenness Index, Dominance Index, and Damage Intensity. According to the study's findings, Bactrocera dorsalis, Bactrocera umbrosa, and Bactrocera cucurbitae were the fruit fly species that were discovered in tomato plantings. The Diversity Index (H') value is 0.7253, which indicates a low level of diversity; the highest Abundance Index (KR) is B. dorsalis with a value of 62.4633%; the Evenness Index (E) is 0.6602 in the even category; and the Dominance Index (D) is 0.4365 in the medium dominance category with a Damage Intensity of 9.76 percent, which is classified as light criteria.